Gasification-based clean conversions and utilizations of coal, oil shale and biomass - Jiang, Peng (2020)
Gasification-based conversion of solid fuels into syngas for power and chemical product generations is regarded as the cleanest and most efficient thermal process. The objectives of this study is to have an in depth understanding of gasification (and co-gasification) of coal, oil shale and biomass in terms of its kinetics, thermodynamics, economics and environmental impacts through the combination of lab experiments and simulations. To summarize, the work carried out in this study can be divided into the following three parts.